PENERAPAN MODEL PROBLEM BASED LEARNING DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA TENTANG SOAL CERITA PECAHAN PADA SISWA KELAS V SD N 1 KEDUNGWINANGUN TAHUN AJARAN 2015/2016 - santoso, bagus (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Problem Based Learning Model in Improving Mathematics Learning about Fraction Problem for the Fifth Grade Students of SD Negeri 1 Kedungwinangun in the Academic Year of 2015/2016. The objective of this research is to improve Mathematics learning about fraction problem through the application of Problem Based Learning for the fifth grade students of elementary schools. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. Techniques of collecting data were observation, interview, documentation, and test. The results of this research show that: the application of Problem Based Learning model can improve Mathematics learning about fraction problem for the fifth grade students of SD Negeri 1 Kedunfwinangun in the academic year of 2015/2016. Keywords: learning model, Problem Based Learning, fractionAbstrak: Penerapan Model Problem Based Learning dalam Peningkatan Pembelajaran Matematika tentang Soal Cerita Pecahan pada Siswa Kelas V SD N 1 Kedungwinangun Tahun Ajaran 2015/2016. Penelitian ini bertujuan untuk meningkatkan pembelajaran tentang soal cerita pecahan dengan menerapkan model Problem Based Learning pada siswa kelas V SD. Penelitian ini adalah penelitian tindakan kelas kolaboratif yang dilaksanakan dalam tiga siklus. Masing-masing siklus mencakup tahap perencanaan, pelaksanaan, observasi dan refleksi. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi, dan tes. Hasil penelitian ini menunjukkan bahwa penerapan model Prblem Based Learning dapat meningkatkan pembelajaran tentang soal cerita pecahan pada siswa kelas V SD N 1 Kedungwinangun tahun ajaran 2015/2016. Kata Kunci: Model Pembelajaran, Problem Based Learning, Pecahan.